Selective cyclooxygenase-2 inhibition protects against myocardial damage in experimental acute ischemia - Alberto Carnieto Jr.; Paulo Magno Martins Dourado; Protásio Lemos da Luz; Antonio Carlos Palandri Chagas (Clinics, 2009)
BACKGROUND: Acute myocardial infarction is associated with tissue inflammation. Early coronary reperfusion clearly improves the outcome but may help propagate the inflammatory response and enhance tissue damage. Cyclooxygenase-2 is an enzyme that catalyzes the initial step in the formation of inflammatory prostaglandins from arachidonic acid. Cyclooxygenase-2 levels are increased when ischemic cardiac events occur. The overall function of COX-2 in the inflammatory process generated by myocardial ischemic damage has not yet been elucidated. GOAL: The objective of this study was to determine whether a selective cyclooxygenase-2 inhibitor (rofecoxib) could alter the evolution of acute myocardial infarction after reperfusion. METHODS AND RESULTS: This study was performed with 48 mongrel dogs divided into two groups: controls and those treated with the drug. All animals were prepared for left anterior descending coronary artery occlusion. The dogs then underwent 180 minutes of coronary occlusion, followed by 30 minutes of reperfusion. Blood samples were collected from the venous sinus immediately before coronary occlusion and after 30 minutes of reperfusion for measurements of CPK-MB, CPK-MBm and troponin I. During the experiment we observed the mean blood pressure, heart rate and coronary flow. The coronary flow and heart rate did not change, but in the control group, there was blood pressure instability, in addition to maximal levels of CPK-MB post-infarction. The same results were observed for CPK-MBm and troponin I. CONCLUSION: In a canine model of myocardial ischemia-reperfusion, selective inhibition of Cyclooxygenase-2 with rofecoxib was not associated with early detrimental effects on the hemodynamic profile or the gross extent of infarction; in fact, it may be beneficial by limiting cell necrosis.